A Survey on Use of Agrochemicals in Farms in Uasin Gishu and Homa Bay Counties, Kenya - Akenga, T.; Sudoi, V.; Machuka, W.; Kerich, E.; Bikeri, E. (Africa Environmental Review Journal, 2017)
The Kenya agricultural sector is an important segment of the national economy generating employment, outputs and incomes. Currently, agriculture directly represents 26 % of the gross domestic product (GDP). Due to the significant contribution of the agricultural sector to the overall economic growth, it is important to invest commensurately in order to meet the targeted growth rate of 6% per year. In trying to expand the agricultural production, farmers face several challenges which include inadequate farm inputs and poor soils. Fertilizers and pesticides are frequently added to soils to supply sufficient nutrients for plant growth which could contribute to environmental pollution. This study was conducted to assess farming practices, agrochemical usage and its potential impact on environment in Uasin Gishu and Homa Bay Counties, Kenya. Field surveys involving key informant interviews and questionnaires were administered to farmers in the study areas of Homa Bay and Uasin Gishu counties. Five sub-locations were randomly sampled from the two regions where intensive farming was practised. The sampling sites were considered in different agro ecological zones. The survey obtained information on the extent of use of agrochemicals and agricultural activities carried out in the two regions. Obtained data was analysed using descriptive statistics. One-Way ANOVA and t-test was used to compare agrochemicals usage in all agro-ecological zones. A total of 384 households were sampled in both regions and showed that farmers used different agricultural chemicals and fertilizers. In Uasin Gishu County 89.8% of farmers used herbicides to weed their farms whereas in Homa bay only a small percentage (28.4%) used herbicides. Other agronomic practices include, manual weeding at 10.2% in Uasin Gishu and 71.6% in Homa Bay county. Use of insecticides was 10.0% in Uasin Gishu County and 9.8% in Homa Bay County. The use of inorganic fertilizers indicated that in Uasin Gishu County, all of the sampled households (100%) used inorganic fertilizers in their farms. A small proportion of farmers (27.4%) in Homa Bay County used inorganic fertilizers. Most of the farmers in Homa Bay County used animal manure (54.2%) while a small number of farmers (19.2%) did not apply any fertilizers in their farms. There was a significant difference in usage of agrochemicals in both counties. These findings show that farmers in both regions use inorganic fertilizers, herbicides and pesticides in their farms and may lead to heavy metal contamination in the soils. Limited knowledge among the farming communities on use of agrochemicals could pose risk to the users and the environment. It is therefore necessary to sensitize farmers on use of organic fertilizers and integrated pest management (IPM).